Hydrologic controls on the accumulation of different sized microplastics in the streambed sediments downstream of a wastewater treatment plant (Catalonia, Spain). (8th November 2021) - Margenat, Henar; Nel, Holly A; Stonedahl, Susa H; Krause, Stefan; Sabater, Francesc; Drummond, Jennifer D
Abstract: Wastewater treatment plants (WWTPs) act as a point source of microplastics (MPs) to freshwater ecosystems. Although MP abundance has been linked to high-density population areas, the mechanisms of how river hydrodynamics and particle size influence MP accumulation in streams are still largely unknown. This study investigated the spatial distribution of MPs within streambed sediments downstream of a WWTP effluent in Cànoves stream (Montseny, Catalonia) during baseflow conditions. MP concentrations from an upstream control site were compared to the WWTP bypass that added untreated wastewater at times when stream discharge exceeded capacity. The 450 m section investigated downstream of the WWTP consisted of three geomorphically altered sub-reaches interspersed between three unaltered buffer sub-reaches, each ∼75 m that provided a range in hydrologic conditions. Measurements of MP characteristics, hydrogeomorphic variables, and fine particles were simultaneously taken. MPs were quantified following the Nile red fluorescence method for large (>64 µ m) and small (10–64 µ m) particles. MPs in sediment samples downstream of the WWTP were mainly fragments with a higher abundance of small MPs (85 particles/g of sediment) vs large MPs (9 particles/g of sediment). While the abundance of large MPs in streambed sediments decreased with distance from the WWTP point source, the abundance of small MPs increased. Furthermore, the area of small MPs decreased with distance from the WWTP. MPs were most abundant at the WWTP bypass, suggesting these infrequent inputs during storm events represent an important source of MPs to the stream. Higher MP abundance coincided with increased organic matter content and smaller sediment grain sizes. Overall, our results present significant findings that could help explain differences in transport and accumulation patterns of MPs that influence their retention times in streambeds, suggesting a combination of preferential filtration in the streambed sediments, and fragmentation of larger particles.